1998
DOI: 10.1073/pnas.95.1.258
|View full text |Cite
|
Sign up to set email alerts
|

A chemokine expressed in lymphoid high endothelial venules promotes the adhesion and chemotaxis of naive T lymphocytes

Abstract: Preferential homing of naive lymphocytes to secondary lymphoid organs is thought to involve the action of chemokines, yet no chemokine has been shown to have either the expression pattern or the activities required to mediate this process. Here we show that a chemokine represented in the EST database, secondary lymphoid-tissue chemokine (SLC), is expressed in the high endothelial venules of lymph nodes and Peyer's patches, in the T cell areas of spleen, lymph nodes, and Peyer's patches, and in the lymphatic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

44
720
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 888 publications
(765 citation statements)
references
References 41 publications
44
720
1
Order By: Relevance
“…Of note, this synergism occurs also in the opposite direction: CCL7 synergizes with CCL19 and CCL21 on CCR7-transfected cells as well as on mature dendritic cells, as we previously described [9]. A meeting place of both homeostatic and inflammatory chemokines is HEV where CCL19 and CCL21 are both expressed [26], and CCL2 and CCL7 [20,42] are transported from inflamed tissue to trigger arrest of rolling monocytes [32]. Therefore, the CCR7 and the CCR2 agonists meet the criteria to be at the same place and at the same time to enhance the migration of CCR2 1 cells in vivo.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Of note, this synergism occurs also in the opposite direction: CCL7 synergizes with CCL19 and CCL21 on CCR7-transfected cells as well as on mature dendritic cells, as we previously described [9]. A meeting place of both homeostatic and inflammatory chemokines is HEV where CCL19 and CCL21 are both expressed [26], and CCL2 and CCL7 [20,42] are transported from inflamed tissue to trigger arrest of rolling monocytes [32]. Therefore, the CCR7 and the CCR2 agonists meet the criteria to be at the same place and at the same time to enhance the migration of CCR2 1 cells in vivo.…”
supporting
confidence: 51%
“…Constitutively expressed chemokines act in primary and secondary lymphoid organs [16,17,26] and peripheral tissues [27,28]. The CCR7 ligands, CCL19 and CCL21 [29,30], are expressed in the T-cell area of secondary lymphoid organs as well as on high endothelial venules (HEV) [31] and orchestrate the migration of CCR7 1 cells.…”
mentioning
confidence: 99%
“…[26][27][28] One of the best candidates for chemokines is CCL21, which has been proposed to play a role in favoring the interactions between DCs and T cells in secondary lymphoid organs through CCR7 receptor. 4,7,9,29 In fact, mice deficient in the expression of CCL21 showed defects in lymphocyte homing and DC localization, 30 and mice lacking CCR7 receptor also had defects in lymph node architecture. 31 Furthermore, it has been demonstrated that CCL21 could participate itself in lymphoid tissue development and organization in a transgenic model where the CCL21 gene was expressed in pancreatic islets.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] DCs are professional antigen-presenting cells (APCs) that play a crucial role in initiation of the immune response of both helper and cytotoxic T lymphocytes. 1 DCs reside in many tissues in an immature state with the ability to capture and process antigens, and acquire a mature phenotype with increased cell surface expression of MHC and costimulatory molecules upon uptake of antigen and response to stimuli such as inflammatory cytokines, necrotic cells, and microbial products.…”
mentioning
confidence: 99%
“…Activation of lymphocytes to induce firm arrest is mediated by tissue-specific chemokines displayed on endothelial surfaces [17]. In mice, HEVs have the ability to produce and display CCL21, the chemokine primarily associated with naïve lymphocyte activation [18,19]. In a truly restricted fashion, CCL21 has the ability to only interact with its specific receptor namely, CCR7, which is uniformly found on naïve and central memory T cells.…”
Section: Process Of Lymphocyte Entry Into Lymph Nodesmentioning
confidence: 99%